2010
DOI: 10.2298/vsp1004273d
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor gene polymorphism could influence renoprotective response to losartan treatment in type 1 diabetic patients with high urinary albumin excretion rate

Abstract: The results of our small sample size study provide the evidence that 1166 A/C AT1R polymorphism could be associated with the renoprotective response to losartan therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Albuminuria is considered as a marker of kidney (glomerular) damage, and the first clinical indicator of DN presence 16 . Even today it is a clinically useful tool for predicting the outcome and for monitoring a response to the therapy 11 . Discordance between the presence of albuminuria and the decline in renal function is crucial point of clinical significance of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albuminuria is considered as a marker of kidney (glomerular) damage, and the first clinical indicator of DN presence 16 . Even today it is a clinically useful tool for predicting the outcome and for monitoring a response to the therapy 11 . Discordance between the presence of albuminuria and the decline in renal function is crucial point of clinical significance of albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that some relevant biomarkers associated with DN were found and they potentially could be used to predict DN or progression of the disease 10 . Several different markers of tubular and glomerular damage were investigated to discover DN in its early phase and to start therapy as soon as possible 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the relationship of AGTR1 polymorphisms with DN showed that the AA genotype of rs5186 was independently associated with overt DN, being with a threefold increase in the risk for the disease compared to AC and CC genotypes (Möllsten et al, 2008). The treatment with renoprotective antihypertensive (losartan) for slowing down the progression of diabetic glomerulopathy reduced significantly albuminuria, systolic and diastolic blood pressure in the A allele vs C allele carriers of rs5186 polymorphism (Dragović et al, 2010). Oppose, the rs5186 of AGTR1 was found not associated with DN in other reports (Gallego et al, 2008;Nosikov, 2004;Tarnow et al, 2000).…”
Section: Other Ras Genesmentioning
confidence: 99%
“…Dragović et al [20] showed that 1166 A/C AGTR1 polymorphism was associated with the renoprotective response to ARB therapy in type 1 diabetic patients. Narita et al [21] observed that M235T and A (-20) C genotype of AGT could influence the therapeutic efficacy of a RAS blockade in immunoglobulin A nephropathy (IgAN).…”
Section: Introductionmentioning
confidence: 99%